Effect of Village Fund Programs on Employment Opportunities, Economic Growth, Poverty Levels, and Equitable Income in Central Kalimantan - Udi Kusdino; Gundik Gohong; Fitria Husnatarina (Journal Magister Ilmu Ekonomi Universtas Palangka Raya : GROWTH, 2018)
ABSTRACTThe purpose of this study was to find out and analyze the influence of village fund programs on employment opportunities, economic growth, poverty levels and income distribution. This study uses a qualitative method with a panel data regression approach. The subjects in this study were all districts that received village funds in Central Kalimantan in 2015-2017, while the object of the study was the influence of village fund programs on employment opportunities, economic growth, poverty levels and even income distribution of the people of Central Kalimantan Province. The method of determining the sample used is purposive sampling. Data collection techniques used in this study are documentation techniques, namely obtaining village fund ceiling data, data on labor force participation rates, poverty rate data, economic growth / GRDP data, and gini ratio data in 13 districts in Central Kalimantan Province for the period of the year 2015-2017. Data was processed with the help of SPSS version 24 software. The results showed that village fund programs had a positive and significant effect on employment opportunities, economic growth and poverty levels in Central Kalimantan Province. While for village programs it does not affect the distribution of income in Central Kalimantan Province.